2021
DOI: 10.1186/s12884-021-04069-w
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-513c-5p is involved in the pathogenesis of preeclampsia by regulating of low-density lipoprotein receptor-associated protein 6

Abstract: Background Preeclampsia (PE) is a major cause of maternal and perinatal morbidity and mortality. Studies on the role of microRNAs (miRNAs), in the pathogenesis of PE through their effects on trophoblast function have been reported, but roles for some miRNAs including miR-513c-5p, have not been identified. We aimed to evaluate potential miRNA candidates that regulate the LRP6 mRNAand to elucidate the possible mechanism in PE. Potential miRNAs were selected by bioinformatics analysis, PCR of plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…MicroRNA (miRNA) is a type of widely existing small molecule non-coding RNA, playing a role in cell proliferation, differentiation, apoptosis, and other processes [14,15]. The expression of miRNA is tissue-speci c, and its abnormal expression may be correlated with the occurrence and development of a wide variety of diseases.PE refers to a placenta-derived disease.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA (miRNA) is a type of widely existing small molecule non-coding RNA, playing a role in cell proliferation, differentiation, apoptosis, and other processes [14,15]. The expression of miRNA is tissue-speci c, and its abnormal expression may be correlated with the occurrence and development of a wide variety of diseases.PE refers to a placenta-derived disease.…”
Section: Discussionmentioning
confidence: 99%
“…The four potential biomarker miRNAs identified in our study have never been linked to RPL before. The expression of miR-145-5p was increased in the placentas of patients with PE (Zhou et al, 2021). Mir-145-5p overexpression inhibited HTR-8/SVneo cell motility and invasion by negatively regulating Cyr61 expression through interactions with its 3′-untranslated region (UTR) (Wen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…miR-513c-5p is a coding product of MIR-513C , which is localized on the human chromosome X. Little is known of miR-513c-5p function, except for some reports indicating that miR-513c-5p might play roles in the progression of thyroid cancer, neuroblastoma, or preeclampsia ( Jia et al, 2020 ; Tong et al, 2021 ; Zhou et al, 2021 ). Our intensive functional and mechanistic investigation demonstrated that miR-513c-5p effectively inhibited caspase-1 expression by binding to its 3′ untranslated region (3′UTR).…”
Section: Introductionmentioning
confidence: 99%